Benign growth: Structural transformation and inclusive growth in Thailand - Peter George Warr; Waleerat Suphannachart (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Between 1981 and 2017, real gross domestic product in Thailand grew at an average annual rate of 5.7 per cent. Agricultural output grew more slowly than industry or services, and its gross domestic product share consequently declined. Industry's gross domestic product share increased, and the share of services remained relatively constant. Agriculture's employment share declined, but most new jobs were in services. Concurrently, poverty incidence declined dramatically. Income inequality increased until the late 1980s, then gradually declined, reaching a level in 2017 that was well below the 1981 level. Economic growth combined with structural change contributed to poverty reduction, but the magnitude of this impact depends heavily on the poverty line used in calculating poverty. The Thai data support the Kuznets hypothesis of an inverted U-shaped relationship between average income and inequality but suggest no long-term 'Kuznetsian tension' between the rate of structural change and the level of inequality.
Keywords: O14; O53; P51; 330; inclusive growth; inequality; poverty reduction; structural transformation; Thailand